ADVANTAGES AND DISADVANTAGES OF MODERN EDUCATIONAL TECHNOLOGIES AND METHODS - Feruza Najmiddinovna Rakhimova (Journals Park Publishing, 2025)
This article provides an in-depth analysis of the advantages and disadvantages of modern educational technologies and interactive teaching methods. It examines the theoretical foundations of interactive approaches based on the pedagogical theories of renowned scholars such as John Dewey, Lev Vygotsky, Jerome Bruner, and Carl Rogers. The article also highlights the effectiveness of these methods in the educational process, their role in developing students’ critical and creative thinking, and their importance in fostering collaboration and communication skills. Additionally, the article discusses the relevance of interactive methods, practical challenges, and provides recommendations for overcoming them. It serves as a valuable resource for teachers, educational researchers, and policymakers.
Keywords: Modern education, interactive methods, learning process, critical thinking, pedagogical approaches, John Dewey, Vygotsky, Bruner, Rogers, educational effectiveness, methodological literacy, education reforms in Uzbekistan.